POSITIVE AND NEGATIVE NUMBERS LESSON 6
ADDING INTEGERS Positive + Positive = Positive ( +3) + (+2) = +5 When a number is positive, you do not have to use the (+) sign. (+3) + (+2) = 5
ADDING TWO NEGATIVE NUMBERS Negative + Negative = Negative (- 6) + (- 3) = - 9 When a number is NEGATIVE, you do have to use the (-) sign.
ADDING POSITIVE AND NEGATIVE INTEGERS Sum of a negative and a positive number - Keep the sign of the larger number and subtract EXAMPLE 1: (- 6) + 3 = -3 COPY DOWN QUESTION
ADDING POSITIVE AND NEGATIVE INTEGERS Sum of a negative and a positive number - Keep the sign of the larger number and subtract EXAMPLE 1: (- 6) + 3 = -3 COPY DOWN QUESTION 6 – 3 = 3 Subtract the numbers without negative signs.
ADDING POSITIVE AND NEGATIVE INTEGERS Sum of a negative and a positive number - Keep the sign of the larger number and subtract EXAMPLE 1: (- 6) + 3 = -3 COPY DOWN QUESTION 6 – 3 = 3 Subtract the numbers without negative signs. = -3 Keep the sign of the larger number.
ADDING POSITIVE AND NEGATIVE INTEGERS Sum of a negative and a positive number - Keep the sign of the larger number and subtract EXAMPLE 2: 9 + (-12) = - 3 COPY DOWN QUESTION
ADDING POSITIVE AND NEGATIVE INTEGERS Sum of a negative and a positive number - Keep the sign of the larger number and subtract EXAMPLE 2: 9 + (-12) = - 3 COPY DOWN QUESTION 12 – 9 = 3 Subtract the numbers without negative signs.
ADDING POSITIVE AND NEGATIVE INTEGERS Sum of a negative and a positive number - Keep the sign of the larger number and subtract EXAMPLE 2: 9 + (-12) = - 3 COPY DOWN QUESTION 12 – 9 = 3 Subtract the numbers without negative signs. = -3 Keep the sign of the larger number.
ADDING POSITIVE AND NEGATIVE INTEGERS Sum of a negative and a positive number - Keep the sign of the larger number and subtract EXAMPLE 3: (- 5) + 7 = 2 COPY DOWN QUESTION
ADDING POSITIVE AND NEGATIVE INTEGERS Sum of a negative and a positive number - Keep the sign of the larger number and subtract EXAMPLE 3: (- 5) + 7 = 2 COPY DOWN QUESTION 7 – 5 = 2 Subtract the numbers without negative signs.
ADDING POSITIVE AND NEGATIVE INTEGERS Sum of a negative and a positive number - Keep the sign of the larger number and subtract EXAMPLE 3: (- 5) + 7 = 2 COPY DOWN QUESTION 7 – 5 = 2 Subtract the numbers without negative signs. = 2 Keep the sign of the larger number.
SUBTRACTING INTEGERS Negative - Positive = Negative (same as adding two negative numbers) (- 8) - 3 = -8 + (-3) = -11 Another way of saying this: ADD THE OPPOSITE
SUBTRACTING INTEGERS Positive - Negative = Positive + Positive = Positive 4 - (-3) = 4 + 3 = 7 Once again you are adding the opposite
SUBTRACTING INTEGERS Negative - Negative = Negative + Positive = Keep the sign of the larger number and subtract (-7) - (-5) = ( -7) + 5 = -2 (-5) - ( -7) = (-5) + 7 = 2
TRY THESE ADD SUBTRACT 1) (+6) + (-2) 1) (7) – (2) 2) (+7) + 3 2) (+8) – (-2) 3) (-5) + (+2) 3) (-9) – (+3) 4) (-6) – (-2)
ADD SUBTRACT 1) (+6) + (-2) = 4 1) (7) – (2) 2) (+7) + 3 2) (+8) – (-2) 3) (-5) + (+2) 3) (-9) – (+3) 4) (-6) – (-2)
ADD SUBTRACT 1) (+6) + (-2) = 4 1) (7) – (2) 2) (+7) + 3 = 10 2) (+8) – (-2) 3) (-5) + (+2) 3) (-9) – (+3) 4) (-6) – (-2)
TRY THESE ADD SUBTRACT 1) (+6) + (-2) = 4 1) (7) – (2) 2) (+7) + 3 = 10 2) (+8) – (-2) 3) (-5) + (+2) = -3 3) (-9) – (+3) 4) (-6) – (-2)
ADD SUBTRACT 1) (+6) + (-2) = 4 1) (7) – (2) = 5 2) (+7) + 3 = 10 2) (+8) – (-2) 3) (-5) + (+2) = -3 3) (-9) – (+3) 4) (-6) – (-2)
ADD SUBTRACT 1) (+6) + (-2) = 4 1) (7) – (2) = 5 2) (+7) + 3 = 10 2) (+8) – (-2) = (+8) + (+2) 3) (-5) + (+2) = -3 3) (-9) – (+3) 4) (-6) – (-2)
ADD SUBTRACT 1) (+6) + (-2) = 4 1) (7) – (2) = 5 2) (+7) + 3 = 10 2) (+8) – (-2) = (+8) + (+2) = 10 3) (-5) + (+2) = -3 3) (-9) – (+3) 4) (-6) – (-2)
ADD SUBTRACT 1) (+6) + (-2) = 4 1) (7) – (2) = 5 2) (+7) + 3 = 10 2) (+8) – (-2) = (+8) + (+2) = 10 3) (-5) + (+2) = -3 3) (-9) – (+3) = (-9) + (-3) 4) (-6) – (-2)
ADD SUBTRACT 1) (+6) + (-2) = 4 1) (7) – (2) = 5 2) (+7) + 3 = 10 2) (+8) – (-2) = (+8) + (+2) = 10 3) (-5) + (+2) = -3 3) (-9) – (+3) = (-9) + (-3) = - 12 4) (-6) – (-2)
ADD SUBTRACT 1) (+6) + (-2) = 4 1) (7) – (2) = 5 2) (+7) + 3 = 10 2) (+8) – (-2) = (+8) + (+2) = 10 3) (-5) + (+2) = -3 3) (-9) – (+3) = (-9) + (-3) = - 12 4) (-6) – (-2) = (-6) + (2)
ADD SUBTRACT 1) (+6) + (-2) = 4 1) (7) – (2) = 5 2) (+7) + 3 = 10 2) (+8) – (-2) = (+8) + (+2) = 10 3) (-5) + (+2) = -3 3) (-9) – (+3) = (-9) + (-3) = - 12 4) (-6) – (-2) = (-6) + (2) = -4